2012
DOI: 10.1007/s11357-012-9384-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining sarcopenia: the impact of different diagnostic criteria on the prevalence of sarcopenia in a large middle aged cohort

Abstract: Sarcopenia, low muscle mass, is an increasing problem in our ageing society. The prevalence of sarcopenia varies extremely between elderly cohorts ranging from 7% to over 50%. Without consensus on the definition of sarcopenia, a variety of diagnostic criteria are being used. We assessed the degree of agreement between seven different diagnostic criteria for sarcopenia based on muscle mass and handgrip strength, described in literature. In this cross-sectional study, we included men (n = 325) and women (n = 329… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
160
3
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(209 citation statements)
references
References 48 publications
13
160
3
17
Order By: Relevance
“…17,30 The prevalence of sarcopenia varies depending on the methods used to define the diagnosis. Bijlsma et al 31 used seven different diagnostic criteria for sarcopenia, based on measurements of muscle mass (BIA or DXA) and HGS. The authors noted that the criteria based on a low HGS and a low quantity of SMM differed greatly from the criteria based on appendicular lean mass (ALM).…”
Section: Discussionmentioning
confidence: 99%
“…17,30 The prevalence of sarcopenia varies depending on the methods used to define the diagnosis. Bijlsma et al 31 used seven different diagnostic criteria for sarcopenia, based on measurements of muscle mass (BIA or DXA) and HGS. The authors noted that the criteria based on a low HGS and a low quantity of SMM differed greatly from the criteria based on appendicular lean mass (ALM).…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, several diagnostic criteria for sarcopenia have been proposed, which can be categorized into measures of relative muscle mass (defined as total or appendicular lean mass (ALM) as percentage of body mass), absolute muscle mass (defined as ALM corrected for height (ALM/height squared) or total lean mass), muscle strength, walking speed, or a combination of criteria (Cruz-Jentoft et al 2010;Fielding et al 2011). Previously, we have shown that the prevalence of sarcopenia is highly dependent on the diagnostic criteria (Bijlsma et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bijlsma et al 18 applied six different formulas to define low lean body mass. Comparatively, low lean mass among men aged 60-69 years varied from 0 to 31% and for those older than 70 years from 0 to 45%.…”
Section: Discussionmentioning
confidence: 99%